Motor learning and development - Haibach-Beach, Pamela S. 1977-; Reid, Gregory D. 1948-; Collier, Douglas Holden 1953- (Human Kinetics, 2018)
This volume provides a foundation for understanding how movement skills are acquired and developed throughout life. These fundamentals give students the tools needed to create, apply and evaluate motor skill programmes for learners and clients. These can then be used with clients at all skill and development levels, from elite athletes to those with severe disabilities.